An empirical investigation of the relationships between manufacturing flexibility and product quality. (1st January 2012) - Nayak, Narayan C.; Ray, Pradip K.
The purpose of this research paper is to investigate the relationships between production system flexibility and product quality. The impetus for this study was initiated by an argument that flexibility and quality are two elements that compete with each other, and that firms need to make a trade-off decision between the two. The relationships between the two operational measures are based on various dimensions of flexibility and different indicators of product quality. This research identified certain gaps in the literature and formulated hypotheses. Using a case study data drawn from a leading automobile engine manufacturing firm in India, the hypothesised relationships are validated developing path models. There exists much theoretical work and case studies on flexibility and quality control, while this research provides basic knowledge for developing a formal process for identifying, implementing and monitoring manufacturing flexibility to achieve acceptable product quality. The relationship between flexibility and quality is relatively limited, especially with respect to specific measures. The study reports the critical findings that have implications for both manufacturers as well as researchers.